TheimportanceofEnglishforpreschool education: TheimportanceofEnglishforpreschool education - G'aniyeva, Hayriniso; Narbayeva, Maftuna (Maktabgacha taʼlim jurnali, 2022)
Englishhasfastbecometheworld'smostwidelyusedand commonlyspokenlanguagetodayandtheneedtolearn English forkids has gone up exponentially with this growth.Most countries have embraced the English Language as a common dominatorin communication acrosswhiletravelingabroadorworkingwithforeigners.It isthis widespreadusethathasdefined itasoneofthe mostinfluentiallanguagesintheworldandassuchmany parentsprefertheirchildrenlearningEnglishasasecond language.